2012
DOI: 10.1093/pasj/64.1.7
|View full text |Cite
|
Sign up to set email alerts
|

VLBI Astrometry of the Semiregular Variable RX Bootis

Abstract: We present distance measurement of the semiregular variable RX Bootis (RX Boo) with its annual parallax. Using the unique dual-beam system of the VLBI Exploration of Radio Astrometry (VERA) telescope, we conducted astrometric observations of a water maser spot accompanying RX Boo referred to the quasar J1419+2706 separated by 1 • .69 from RX Boo. We have measured the annual parallax of RX Boo to be 7.31 ± 0.50 mas, corresponding to a distance of 136 +10 −9 pc, from the one-year monitoring observation data of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…(Kamezaki et al 2012). Of particular interest are the astrometric measurements for the symbiotic system R Aqr (Kamohara et al 2010) and the parallax distance of 218…”
Section: Asymptotic Giant Branch Starsmentioning
confidence: 99%
“…(Kamezaki et al 2012). Of particular interest are the astrometric measurements for the symbiotic system R Aqr (Kamohara et al 2010) and the parallax distance of 218…”
Section: Asymptotic Giant Branch Starsmentioning
confidence: 99%
“…All references are given in Tables A.1-A.4. For the S-type stars, a comparison between the IRAM 30 m line intensities published in Wallerstein et al (2011) and in Ramstedt et al (2009) Kamezaki et al (2012). (b) Vlemmings et al (2003).…”
Section: Co Radio Line Observationsmentioning
confidence: 99%
“…An apparent K−band magnitude of −1.85 is converted to an absolute magnitude of −7.35 +0.15 −0.14 mag based on the parallax measurement. This source is reported to have different pulsation periods pulsation periods, which are summarised in table 4 of Kamezaki et al (2012). We found that they can be classified into two typical values, ∼160 days and over ∼ 320 days.…”
Section: Semi-regular Variable Rx Boomentioning
confidence: 79%
“…From the position of the source on log P − M K plane, one can study the stellar structure and pulsation properties. Kamezaki et al (2012) compared the M K and dual periods with the P-L relation in the Magellanic Clouds (Ita et al, 2004). Then it was found that RX Boo belongs to the sequence C (pulsating in fundamental mode) at longer period, and belongs to the sequence C' (pulsating in first-over tone mode) at shorter period.…”
Section: Semi-regular Variable Rx Boomentioning
confidence: 99%